Numerical investigation of local defectiveness control of diblock copolymer patterns - Jeong, D.; Choi, Y.; Kim, J. (Condensed Matter Physics, 2016)
We numerically investigate local defectiveness control of self-assembled diblock copolymer patterns through
appropriate substrate design. We use a nonlocal Cahn-Hilliard (CH) equation for the phase separation dynamics
of diblock copolymers. We discretize the nonlocal CH equation by an unconditionally stable finite difference
scheme on a tapered trench design and, in particular, we use Dirichlet, Neumann, and periodic boundary conditions. The value at the Dirichlet boundary comes from an energy-minimizing equilibrium lamellar profile. We
solve the resulting discrete equations using a Gauss-Seidel iterative method. We perform various numerical experiments such as effects of channel width, channel length, and angle on the phase separation dynamics. The
simulation results are consistent with the previous experimental observations. Проведено числове дослiдження керування локальною дефектнiстю самоорганiзованих структур дiблоккополiмерiв за допомогою вiдповiдної конструкцiї субстрату. Використовується нелокальне рiвняння
Кана-Хiлларда для динамiки фазового роздiлення дiблок-кополiмерiв. Здiйснено дискретизацiю нелокального рiвняння з використанням безумовно стiйкої схеми скiнченної рiзницi на звуженiй канавцi зразка i,
зокрема, використано крайовi умови Дiрiхле, Ньюмана i перiодичнi граничнi умови. Значення при крайових умовах Дiрiхле отримано згiдно з рiвноважним ламеларним профiлем, що вiдповiдає енергетичному мiнiмуму. Ми розв’язуємо отриманi дискретнi рiвняння, використовуючи iтеративний метод ГауссаЗейделя. Проведено рiзнi числовi експерименти, такi як вплив ширини каналу, довжини каналу та кута
на динамiку фазового роздiлення. Результати симуляцiй вiдповiдають попереднiм експериментальним
спостереженням.